Reliability of the Single-Visit Field Test of Critical Speed in Trained and Untrained Adolescents - Alfred Nimmerichter; Mathias Steindl; Craig Anthony Williams (MDPI AG, 2015)
Recent studies in adults have shown that the critical intensity during running and cycling estimated from three prediction trials interspersed by 30 min is valid and reliable. To establish the reliability of the single-visit field test to determine critical speed (CS) and the distance above critical speed (D') in adolescents, 29 trained and 14 untrained participants (mean ± SD age: 17.5 ± 0.5 years) performed three tests on a 400-m outdoor track separated by 48 h. Each test consisted of three distances selected to result in finishing times between 2 and 15 min that must be completed as fast as possible. CS and D' were modeled using the linear 1/time model (Speed = D'(1/t) + CS). While the coefficient of variation (CV) of CS was between 2.4% and 4.3%, the CV of D' was 9.3% to 13.6%. Also the intraclass correlation coefficient ranged from 0.919 to 0.983 for CS and from 0.325 to 0.828 for D'. The results show that the single-visit field test provides reliable estimates of CS but not D' in trained and untrained adolescents.